The «constitutionalization» of private law - Mantilla Espinosa, Fabricio (2007)
The more and more recurrent application of constitutional norms in the deprived Right, and more indeed, in the particular relations that a part of the doctrine has called to constitutionalize of the deprived right, nevertheless does not constitute an absolutely accurate expression when not expressing with exactitude the way how these norms are applicable to private relations. Aware of that, the author makes some precisions on which he understands by constitutionalize, afterwards, he approaches to the concept of the application of the constitutional principles with the purpose of highlighting the darkness of the language of the contemporary constitutional right hidden by complex theories whose purpose is not more than to create an appearance of objectivity, justice and scientific rigor that confers to the decisions of the constitutional judges the cuasi incontrovertible